The Cultural Formulation Interview—Generating distance or alliance? A qualitative study of practice changes in Danish mental healthcare. (December 2022) - Lindberg, Laura Glahder; Carlsson, Jessica; Kristiansen, Maria; Skammeritz, Signe; Johansen, Katrine Schepelern
This article presents provider experiences with the Cultural Formulation Interview (CFI) in Danish mental healthcare for migrant patients. Semi-structured interviews with 17 providers and 20 recorded CFI sessions were analyzed with a constructivist grounded theory approach. Based on our empirical material, we endorse the CFI's ability to facilitate working alliance and a profound and contextually situated understanding of the patient. Further, the CFI supported less-experienced providers in investigating cultural issues. Conversely, we found that CFI questions about cultural identity and background evoked notions of distance and 'othering' in the encounter. Nine providers had felt discomfort and professional insecurity when the CFI compelled them to introduce explanatory frameworks of culture in the mental health assessment. Eleven providers had experienced that the abstract nature of the questions inhibited patient responses or led to short and stereotypical descriptions, which had limited analytical value. We describe the contradictory CFI experiences of alliance versus distance at three levels: 1) at the CFI instrument level; 2) at the organizational level; and 3) at the contextual and structural level. We demonstrate benefits and pitfalls of using the CFI with migrants in Denmark, which is an example of a European healthcare context where cultural consultation is not an integrated concept in health education programs and where the notion of culture is contentious due to negative political rhetoric on multiculturalism. We suggest that the CFI should be introduced with thorough training; focus on fidelity; and supervision in the clinical application and understanding of the concept of culture.